Non-target bioactive compound profiles of coffee roasts and preparations. (15th October 2022) - Stiefel, Constanze; Lindemann, Bernd; Morlock, Gertrud E.
Graphical abstract: Highlights: Coffee beans roasted differently and coffees prepared differently were studied for effects. Storage conditions influenced the bioactive potential of the coffee brews. Antioxidative components were identified using HPTLC-EDA-MS. Chlorogenic acid, caffeine, caffeoyl-β-d -glucopyranoside and melanoidines were highly active. Caffeine and chlorogenic acid as important quality parameters were exemplarily quantified. Abstract: Coffee is an inherent part of our daily nutrition and seems to have protective effects against diseases, whereby it is often not fully understood, which ingredients are responsible for the observed effect. Hence, a non-targeted bioactivity profiling was developed to investigate 27 hand-filtered coffee brews of differently roasted coffee beans and 14 differently prepared and stored coffee brews. After separation, multi-imaging, and densitometry, six planar effect-directed assays were performed to reveal individual antioxidative, antibacterial, anti-cholinesterase, anti-diabetic, and estrogenic effects. Individual compounds were mainly responsible for the observed effects, e.g. 5- O -caffeoylquinic acid regarding antioxidative potential and α-glucosidase inhibition, while coffee brews made by a fully automated coffee machine showed the highest antioxidative potential. Unlike preparation and storage conditions, applied roasting conditions and origin of coffee samples played a less important role. Therefore, the way we daily consume our coffee has an impact on the magnitude of potential health effects.